Analysis of justification of importance of study in empirical research articles by non-native english scholars in Malaysia - Soong, Gze Peng. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study investigated the academic writing styles of non - native English scholars in justifying the importance and contribution of their studies in applied linguistic empirical research articles published in Malaysian journals. It examined the st ructural and linguistic features of rationalizing the importance of studies in introduction and closure sections. The 50 research articles were selected from 7 online Malaysian journals. The structural analysis of justification of importance of study were adapted from Swales’ revised 2004 CARS model and Yang and Allison moves and steps of closure sections (2003). The framework for analysis of language features were adapted from Martín - Martín (2008) hedging and adopted from Hyland (2001) self - mention terms. The results revealed that many scholars did not provide a strong argument on the importance of their studies in introduction sections by anchoring it in the literature while the contribution of study in closure sections was adequate. However, there was a l ack of justifying the contribution of study in the Discussion sections. This was probably due to the preference of NNES scholars to write contribution of studies in Conclusion and Pedagogic Implications sections unless only Discussion sections were present . Besides, the structure of justification of studies in the examined sections were recursive and non - linear. This was likely due to the recursive nature of writing. Meanwhile, the linguistic analysis showed that non - native English scholars frequently used hedging in making tentative claims on the contribution of their studies but did not often employ self - mention terms. Hedging was often used to make vague and uncertain claims on the need to conduct the current study due to the lack of empirical literature on the research problem and the broad contributions of the study. It was also used to mention how the findings of the studies might lead to future research and how the findings might be applicable in language teaching and learning. Although there was a lac k of usage in self - mention terms, the scholars generally preferred to use first person pronouns. The lack of using self - mention terms may be due to the preference of reducing personal attributions and probably the lack of self - confidence in portraying thei r scholarly identities in the research articles. Thus, this study may have implication in the teaching and material development of academic and research writing for university students and novice researchers.